FACTORS ASSOCIATED WITH QUALITY OF LIFE AMONG PEOPLE LIVING WITH HIV/AIDS ON HIGHLY ACTIVE ANTI RETROVIRAL THERAPY: A CROSS-SECTIONAL STUDY - SURYANA, KETUT; SUHARSONO, HAMONG; JOENPUTRI, NOVIANA (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To assess Quality of life (QoL) and its associated factors in people living with HIV/AIDS (PLWHA) who taking highly active antiretroviral therapy (HAART) in Wangaya Hospital in Denpasar, Bali, Indonesia. Methods: A cross-sectional study was conducted during February 2019 to January 2020 at Wangaya Hospital in Denpasar, Bali, Indonesia. QoL was assessed using the five-level version of the EuroQol five-dimensional questionnaire (EQ-5D-5L), EQ-5D index value, and the EuroQol visual analogue scale (EQ-VAS). The data was analyzed using Statistical Package for Social Science (SPSS) software package version 26.0. Bivariate analysis was tested using the cross-tabulation Gamma, Kruskal-Wallis and post hoc Mann-Whitney test. P value<0.05 was considered as statistically significant. Results: A total of 584 PLWHA took HAART for at least 3 mo. The median index value and EQ-VAS were 1.0 (range-0.514–1.0) and 100.00 (range 30-100), respectively. Most patients had problems in ‘anxiety/depression’ and ‘pain/discomfort’ domains. Predictors of better QoL included men, married, good adherence, and treatment duration>24 mo (p<0.05). Predictor of poorer QoL included an advanced HIV clinical stage(p=0.001). Conclusion: The QoL scores of PLWHA receiving HAART in our study were high; hence the QoL of PLWHA was good. The good QoL can be taken as the goal for HIV treatment in order to have a successful HAART therapy.